Performance of Semiautomatic Assessment of Carotid Artery Stenosis on CT Angiography: Clarification of Differences with Manual Assessment - Marquering, H.A. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Semiautomated methods for ICA stenosis measurements have the potential to reduce interobserver variability and to speed up its analysis. In this study, we estimate the precision and accuracy of a semiautomated measurement for carotid artery stenosis degree and identify and explain differences compared with the manual method. MATERIALS AND METHODS: In this retrospective study involving 90 patients, 2 observers determined the stenosis degree twice, with both the semiautomated and the manual method. Intra- and interobserver correlations were calculated for both methods. The accuracy was estimated by comparing average semiautomated with manual measurements. The semiautomated stenosis calculations were performed using either the minimal or maximal intersection at the reference site. Individual cases with large differences in measurement were retrospectively inspected by 3 observers. RESULTS: Intra- (R = 0.93, 0.96) and interobserver (R = 0.98) correlations for the semiautomated method were excellent and exceeded the manual performance correlations (R = 0.87, 0.86). The semiautomated measurements correlated well with the manual measurements (R = 0.87), with high specificity of 96% and lower sensitivity of 63%. Large differences were caused by misinterpretations of the semiautomated method associated with calcified plaques, resulting in overestimations of the minimal diameter, underestimation of stenosis degree, and incorrect centerlines. The effect of using the minimal diameter at the reference position resulted in a small, but significant, underestimation of the stenosis degree by the semiautomated method. CONCLUSIONS: The semiautomated method showed an excellent reproducibility and good correlation with manual measurements with a high specificity and lower sensitivity for detecting a significant stenosis. Erroneous semiautomatic stenosis measurements were associated with the presence of calcium.